Effects of Enhanced P2X1 Receptor Ca2+ Influx on Functional Responses in Human Platelets - Rolf, Michael G.; Mahaut-Smith, Martyn P. (Thrombosis and Haemostasis, 2002)
G-protein-coupled P2Y1 and P2Y12 receptors play key roles in platelet activation, however the importance of ionotropic P2X1 receptors remains unclear. Platelet P2X1 responses are highly labile in vitro, but were greatly enhanced by increasing [Ca2+]o in the range 1–10 mM. The P2X1 agonist α,β-MeATP stimulated a shape change which saturated at peak [Ca2+]i of ≥ 400 nM, without evidence for aggregation. The maximal P2X1-evoked transmission decrease was 82% of that obtained via P2Y1 receptors. α., β-MeATP caused a disc to sphere transformation in virtually all platelets, but lacked the long processes produced by ADP. Following block of P2Y1 receptors with A3P5PS, co-stimulation with α., β-MeATP and ADP failed to induce aggregation despite the generation of peak [Ca2+]i responses similar to those stimulated via P2Y1 receptors. Therefore early, transient Ca2+ influx via P2X1 receptors can contribute to platelet activation by stimulating a significant morphological change, but does not readily synergise with P2Y12 receptors to support aggregation.
Keywords: P2X1; shape change; aggregation; platelets; P2Y